Collecting Educational Media : Making, Storing and Accessing Knowledge (Berghahn Books, 2022)
Over the last two centuries, collectors from around the world have historicized, politicized, and digitized media in the pursuit of knowledge and education. This collected volume explores collections of educational media and their bearing on the ways in which people learn in both the present and future, how and why material objects have been used worldwide to store and maintain knowledge for politically expedient reasons, and how our understanding of digital collections can be adequately understood only in relation to, and as an extension and adaptation of, the historically contingent material collections from which they emerged.